Os jogos de papéis sociais no contexto da educação infantil: concepções e práticas docentes - Santos, Rafaela Raíssa Araújo dos (2024)
In childhood, playing is fundamental to promoting development and learning. The relevance of this activity for children's global development was defended by authors such as L. S. Vigotski and D. Elkonin, authors who are the basis for this research. As a guiding activity in the first years of life, play encourages children to appropriate cultural artifacts, and helps improve mental functioning and social exchanges. In the period between 3 and 6 years old, social role playing is conceived as a guiding activity for development. Given its relevance in development, especially in childhood, it is essential that children establish interactions with more experienced people in the culture that, intentionally, enhance episodes of this type of play. In this dissertation, this issue was explored within the scope of Early Childhood Education, a context in which pedagogical intervention is fundamental to mobilize development processes. Therefore, the general objective of this study was to understand and analyze the conceptions and actions of teachers with regard to social role games in Early Childhood Education. As part of this research, a survey of the literature on social role playing was carried out and the presence of studies on the topic was verified, the majority of which came from Postgraduate Programs in Education. It can also be seen that research relates social role playing to aspects of psychic development, such as psychological functions, the role of the teacher in relation to this playing, in addition to studies on the topic with autistic children. The field research included the participation of 31 teachers who work in Early Childhood Education at public institutions in the city of João Pessoa-PB, in the 'pre I' and 'pre II' classes. In a private place at the institution, the professionals responded individually to a sociodemographic questionnaire and a semi-structured interview that included the use of three images of social role play situations. The interviews were carried out after signing the Free and Informed Consent Form, recorded and transcribed verbatim for content analysis that followed the general guidelines of Bardin (2000). The results of the sociodemographic questionnaire demonstrated that all professionals are female. The majority are between the ages of 41 and 50, graduated in Pedagogy between 2011 and 2020, from a private institution. Among the participants, twelve attended postgraduate studies, the majority between 2011 and 2020 at private institutions. The contents arising from the interview were organized into nine axes of analysis generated from the research objectives and the interview script. The results demonstrated that the types of play identified by the teachers among the children corresponded to those that made reference to actions linked to the family, professions developed in society, domestic work, social activities, and acting out children's stories or superheroes. The places where these games occur most frequently mentioned by professionals were: living room, patio, playground, park, outdoor area, library, toy library and corridors. All teachers were unaware of the name ‘social role playing game’, however, they reported witnessing these games among children during their practices and interactions with them, after describing this activity at the time of collection. When asked about what they knew about social role playing, the answers converged on content related to imitating the actions of adults, dramatizing and reproducing their experiences, mainly those of those closest to them. For teachers, this game can promote social relationships/interactions; develop skills and behaviors, facilitate the choice of profession or prepare children for the future. Regarding the teaching role in this game, mediation, guidance, 7 observation, interaction, playing together, directing, encouraging and intervening were cited as the focus of action. Most teachers stated that dialogues about this type of joke had never occurred at the institution where they work. In view of the above, it appears that, through research, it was possible to insert the concept of social role play and verify its occurrence in teaching work, generate reflections and awaken the interest of teachers in this type of play. The importance of, in the pedagogical context, the social role-playing game being conceived by educators as an activity that is the product of historical social relations, which produce children's appropriation of sociocultural tools and modes of interactions with society, is emphasized. Therefore, the relevance of knowledge from the field of Developmental Psychology is defended to collaborate with reflections and proposition of pedagogical practices that enhance children's psyche.